LEGAL AND ORGANIZATIONAL MECHANISMS OF ENVIRONMENTAL POLICY IN UZBEKISTAN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In this article, the elimination of current global ecological problems, the need for the state to provide legal and practical support of environmental activity of citizens, as well as the formation of ecological consciousness, cultural understanding through close acquaintance of the population with ecology and environmental documents, the development of people's ecological outlook, as well as the use of effective methods of education in the field of ecology is maintained.